Effects of variations in compressive strength and fibre content on dynamic properties of ultra-high performance fibre-reinforced concrete. (20th January 2019) - Othman, H.; Marzouk, H.; Sherif, M.
Highlights: The loading rate dependent mechanical properties of UHP-FRC is investigated. Influences of compressive strength and fibre content on mechanical properties of UHP-FRC are addressed. Increasing fibre content (1.0–3.0%) enhances tensile properties and post-peak ductility. Increasing fibre content (1.0–3.0%) has limited effect on compression properties. Dynamic enhancement in flexural strength is inversely proportional to fibre content. Abstract: This research investigates the loading rate dependent compressive strength, elastic modulus, and flexural strength of ultra-high performance fibre reinforced concrete (UHP-FRC). This investigation is motivated by the lack of dynamic increase factor (DIF) models that can be used in dynamic numerical analysis of UHP-FRC. Five UHP-FRC series incorporating three different matrix strength (110, 130, 150 MPa); and three different fibre volume content (1.0, 2.0, and 3.0%) are tested at six different strain rates ranging from the quasi-static (10 −6  s −1 ) to impact level (5 s −1 ). Experimental results have revealed that increasing fibre volume content from 1.0 to 3.0% significantly increases the quasi-static tensile properties and post-peak ductility, however, it has a limited effect on quasi-static compression properties; the dynamic enhancement in the flexural (tensile) strength is inversely proportional to the fibre content. On the other hand, the effect of fibre content on the enhancement of compressive strength and elastic modulus is insignificant.